Pertuzumab Plus High-Dose Trastuzumab in Patients With Progressive Brain Metastases and HER2-Positive Metastatic Breast Cancer: Primary Analysis of a Phase II Study. Issue 24 (20th August 2021) - Lin, Nancy U.; Pegram, Mark; Sahebjam, Solmaz; Ibrahim, Nuhad; Fung, Anita; Cheng, Anna; Nicholas, Alan; Kirschbrown, Whitney; Kumthekar, Priya
Abstract : PURPOSE: Effective therapies are needed for the treatment of patients with human epidermal growth factor receptor-2 (HER2)-positive metastatic breast cancer (MBC) with brain metastases. A trastuzumab radioisotope has been shown to localize in brain metastases of patients with HER2-positive MBC, and intracranial xenograft models have demonstrated a dose-dependent response to trastuzumab. METHODS: In the phase II PATRICIA study (ClinicalTrials.gov identifier: NCT02536339 ), patients with HER2-positive MBC with CNS metastases and CNS progression despite prior radiotherapy received pertuzumab plus high-dose trastuzumab (6 mg/kg weekly) until CNS or systemic disease progression or unacceptable toxicity. The primary end point was confirmed objective response rate (ORR) in the CNS per Response Assessment in Neuro-Oncology Brain Metastases criteria. Secondary end points included duration of response, clinical benefit rate (complete response plus partial response plus stable disease ≥ 4 or ≥ 6 months) in the CNS, and safety. RESULTS: Thirty-nine patients were treated for a median (range) of 4.5 (0.3-37.3) months at clinical cutoff. Thirty-seven patients discontinued treatment, most commonly because of CNS progression (n = 27); two remained on treatment. CNS ORR was 11% (95% CI, 3 to 25), with four partial responses (median duration of response, 4.6 months). Clinical benefit rate at 4 months and 6 months was 68% and 51%, respectively. Two patients permanently discontinued study treatment because of adverse events (left ventricular dysfunction [treatment-related] and seizure, both grade 3). No grade 5 adverse events were reported. No new safety signals emerged with either agent. CONCLUSION: Although the CNS ORR was modest, 68% of patients experienced clinical benefit, and two patients had ongoing stable intracranial and extracranial disease for > 2 years. High-dose trastuzumab for HER2-positive CNS metastases may warrant further study.